Estimation of Nuclear Genome Size of Three Species of Camponotus (Mayr, 1861) (Hymenoptera: Formicidae: Formicinae) and Their Cytogenetic Relationship - Aguiar, Hilton Jeferson Alves Cardoso de; Barros, Luísa Antônia Campos; Soares, Fernanda Aparecida Ferrari; Carvalho, Carlos Roberto de; Pompolo, Silvia das Graças (Sociobiology, 2016)
The chromosome variability among ant species is remarkable, and the processes generating such variation are still under discussion since polyploidy has been observed in some distinct taxa. The chromosome number of species belonging to the Camponotus, subgenera Myrmothrix and Myrmobrachys, are highly different, whereas, the first subgenus has double the number of chromosomes of the second. In order to test the hypothesis of chromosome number doubling through polyploidy, the genome sizes of Camponotus (Myrmothrix) rufipes, Camponotus (Myrmothrix) renggeri and Camponotus (Myrmobrachys) crassus were estimated by flow cytometry. The chromosome number of specimens from the nests studied was also defined. No significant variation was noted in the genome size among them. The mean haploid genome size value (1C) of workers for the three species was 286.16 Mpb (0.29 pg). The polyploidy hypothesis can be ruled out as an evolutionary step linking the karyotype variations among the three studied species since the genome size of C. crassus with 2n = 20 chromosomes was the same as that of C. rufipes and C. renggeri with 2n = 40. The lack of variation in the amount of DNA between the related species C. rufipes and C. renggeri also demonstrate that flow cytometry is not an adequate approach to distinguish them. Our results highlight the importance of combining distinct methods, DNA quantification, and cytogenetics from the same colony. Understanding the path of chromosome evolution of three species with distinct degrees of relatedness should provide further information in enriching our knowledge about the Minimum Interaction Theory.